Impact of Interpersonal Relations on the Mental Health of College Students - Lang, Yueqian (Transactions on Social Science, Education and Humanities Research, 2024)
Over the years, mental health has become a hot issue, and it seems that after the rampant COVID-19, increasingly numbers of people have suffered from mental distress. Especially for college students who are in the transition period from teenagers to adulthood, it is valuable to explore the conditions of their mental health, for mental well-being may affect students' academic performances, interpersonal relationships, and even their future. This article will focus on one of the most important factors that may influence students' mental status, namely, interpersonal relationship. Three types of relationships that are common and predominant in students' social networks will be discussed in the article by comprehensively analyzing previous studies and students' mental health. As a result, it is transparent that both family relationships, peer relationships and romantic relationships are related to students’ mental health, and some studies also revealed that diagnose histories are often associated with poor social conditions. Therefore, this paper is aiming to focus on the influences of multiple types of interpersonal relationships that may result in mental disorders and provide possible prospects for future study.